A Critical Need for Advanced Practice Nurse Education in Sub‐Saharan Africa and Lessons Learned From the COVID‐19 Pandemic: A Discursive Review - Jacqueline Itambo; Brenda Owusu; Danielle McCamey; Diana‐Lyn Baptiste (Nursing Open)
ABSTRACT Aim To discuss the need to expand advanced practice nurse education in Sub‐Saharan Africa as a strategic response to the impact of the COVID‐19 pandemic. Design Discursive paper. Method Searching international literature in PubMed, CINAHL and Google Scholar databases, we explored the impact of COVID‐19 in Sub‐Saharan Africa and the advanced practice nurse role and education in the pandemic response. Discussion The COVID‐19 pandemic served as a barrier to healthcare access and disrupted routine immunizations and care, reduced facility‐based healthcare services, increased disease burden and mortality, strain and is expected to worsen the healthcare workforce shortage in Sub‐Saharan Africa. The COVID‐19 pandemic has further emphasised the necessity to strengthen advanced practice nurse education in Sub‐Saharan Africa. Conclusion This discursive paper underscores the critical role of advanced practice nurse education in Sub‐Saharan Africa as a proactive strategy to strengthen the healthcare workforce and systems. The lessons learned from the COVID‐19 pandemic highlight the urgency to invest in advanced practice nurse education and training programmes in the region. Patient or Public Contribution There was no patient or public involvement in the design or drafting of this discursive paper. The authors reviewed the literature to develop a discussion about advanced nursing practice.